2021
DOI: 10.3389/falgy.2021.769728
|View full text |Cite
|
Sign up to set email alerts
|

Abundance and Stability as Common Properties of Allergens

Abstract: There have been many attempts to identify common biophysical properties which differentiate allergens from their non-immunogenic counterparts. This review will focus on recent studies which examine two such factors: abundance and stability. Anecdotal accounts have speculated that the elevated abundance of potential allergens would increase the likelihood of human exposure and thus the probability of sensitization. Similarly, the stability of potential allergens dictates its ability to remain a viable immunogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 162 publications
(196 reference statements)
0
26
1
Order By: Relevance
“…Interestingly, recent studies reported differences in biophysical properties and structural dynamics between shrimp and pig tropomyosins, despite their high degree of conservation, which may explain differences in their allergenic potential (James et al, 2018 ; James and Nanda, 2020 ). Finally, although abundance might not be a universal characteristic of all food allergens, it seems to be a predisposing factor that enhances their chance to interact with the immune system, when coupled with other biochemical characteristics, that could produce a food allergen (Bannon, 2004 ; Foo and Mueller, 2021 ).…”
Section: Assessmentmentioning
confidence: 99%
See 3 more Smart Citations
“…Interestingly, recent studies reported differences in biophysical properties and structural dynamics between shrimp and pig tropomyosins, despite their high degree of conservation, which may explain differences in their allergenic potential (James et al, 2018 ; James and Nanda, 2020 ). Finally, although abundance might not be a universal characteristic of all food allergens, it seems to be a predisposing factor that enhances their chance to interact with the immune system, when coupled with other biochemical characteristics, that could produce a food allergen (Bannon, 2004 ; Foo and Mueller, 2021 ).…”
Section: Assessmentmentioning
confidence: 99%
“…Nevertheless, there are possibly a few distinct biochemical characteristics associated with the different protein families that mainly correlate to the elicitation capacity of certain allergens. These characteristics are determined by the 3D structure of proteins, which confer the physicochemical and biological properties governing protein stability, such as the capacity to bind ligands (ranging from metal ions to lipids) and/or resistance to protease degradation and thermal stability (Radauer et al, 2008 ; EFSA GMO Panel, 2017 , 2021 ; Foo and Mueller, 2021 ). Ligands generally increase the stability of allergens to thermal and/or proteolytic degradation (Moreno et al, 2005 ; Vassilopoulou et al, 2006 ; Bossios et al, 2011 ; Berecz et al, 2013 ; Petersen et al, 2014 ) and can also act as immunomodulatory agents that favour Th2 polarisation.…”
Section: Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, food processing often leads to a decrease in allergenicity [ 9 , 10 , 11 , 12 ], although no change, or even an increase, have also been reported for foods such as fish [ 13 ] and peanut [ 14 , 15 ]. Therefore, the combination of different factors and different types of processing methods can be exploited to obtain foods with lower allergenicity having a lower sensitizing power [ 16 ], which can also be consumed by some specific sub-populations of allergic patients. In fact, an increasing number of studies are currently in progress to test the effectiveness of several classic and emerging processing methods in the reduction of the allergenicity of specific foods [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%